(untitled) (Bangladesh Journal of Pharmacology, 2017)
The present study determines the anti-arthritic potential of Ephedra gerardiana ethanolic extract and its ethyl acetate, n-butanol and aqueous fractions adopting in vitro and in vivo tests. In vitro tests included thermally induced bovine serum albumin denaturation and egg albumin denaturation, also membrane stabilizing assay at concentration of 50-6400 µg/mL, whereas in vivo study comprised formaldehyde-induced arthritis at 50, 100 and 200 mg/kg doses. The crude extract and fractions inhibited protein denaturation and stabilized red blood cells membrane in concentration-dependent fashion, with maximal effect achieved at 6,400 µg/mL (p<0.001). Similarly, in formaldehyde model, the extract and fractions dose-dependently reduced injected paw volume and diameter, with maximum reduction at 200 mg/kg (p<0.001). However, results of aqueous fraction were on a par with hydroalcoholic extract in each test. These results suggest that E. gerardiana provides protection against arthritis that might be owing to the existence of phytoconstituents thus, supporting folkloric claim. Video Clip of Methodology: 23 min 48 sec: Click to watch